PERPUSTAKAAN BERBASIS INKLUSI SOSIAL UNTUK PEMBANGUNAN SOSIAL-EKONOMI MASYARAKAT - Dian Utami; Wahyu Deni Prasetyo (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
National development which culminates in the welfare of society must be supported by activities that can accelerate the socio-economic development. Socio-economic development and education and literacy development are, in fact, two interrelated variables and closely connected to improve the human life and community welfare. By accelerating the two developments, the government hopes to stop poverty. Library as an institution fostering literary community should face the challenge with improvements in order to quickly achieve the goal of the national development. Library should be able to focus its activities and programs on social inclusion-based services. The transformation of social inclusion-based library services is an approach by library focused on services committed to increasing the level of the community welfare.